Analysis of The Influence of Absence Levels and Work Discipline on Employee Performance at STIE Mahardhika - Herdijanto, Teguh (Universitas Pamulang, 2023)
In this study using variables including Absenteeism Level as a variable (X1), Work Discipline as a variable (X2) and Employee Performance as a variable (Y). This research was carried out in order to determine the effect of the level of absenteeism and work discipline on the performance of STIE Mahardhika Surabaya employees. Primary data is the data used in this study obtained from questionnaires in the form of a Google form. The hypothesis put forward in this study is that the level of absenteeism and work discipline have an influence on the performance of STIE Mahardhika Surabaya employees. To measure the effect of these variables, multiple linear regression was used using a computer application program, namely IBM SPSS 25. From the results of data analysis using statistical methods, namely multiple linear regression, the results obtained from the R Square or coefficient of determination were 46.6%. The partial test results (t test) explain that the absentee level variable has a significant influence on employee performance with a t count of 2.816 > t table of 2.03951. work discipline variable has a significant influence on employee performance with the acquisition of t count 3.522 > t table 2.03951. Based on these results, it can be concluded that the influence of absenteeism level and work discipline has an effect on employee performance at STIE Mahardhika Surabaya.